Activation of TLR4 by viral glycoproteins: A double-edged sword? - Halajian, Emily A.; LeBlanc, Emmanuelle V.; Gee, Katrina; Colpitts, Che C. (Frontiers in Microbiology, 2022)
Recognition of viral infection by pattern recognition receptors is paramount for a successful immune response to viral infection. However, an unbalanced pro-inflammatory response can be detrimental to the host. Recently, multiple studies have identified that the SARS-CoV-2 spike protein activates Toll-like receptor 4 (TLR4), resulting in the induction of pro-inflammatory cytokine expression. Activation of TLR4 by viral glycoproteins has also been observed in the context of other viral infection models, including respiratory syncytial virus (RSV), dengue virus (DENV) and Ebola virus (EBOV). However, the mechanisms involved in virus-TLR4 interactions have remained unclear. Here, we review viral glycoproteins that act as pathogen-associated molecular patterns to induce an immune response via TLR4. We explore the current understanding of the mechanisms underlying how viral glycoproteins are recognized by TLR4 and discuss the contribution of TLR4 activation to viral pathogenesis. We identify contentious findings and research gaps that highlight the importance of understanding viral glycoprotein-mediated TLR4 activation for potential therapeutic approaches.